2004
DOI: 10.1007/s00018-004-4146-4
|View full text |Cite
|
Sign up to set email alerts
|

HAb18G/CD147-mediated calcium mobilization and hepatoma metastasis require both C-terminal and N-terminal domains

Abstract: HAb18G/CD147 is a heavily glycosylated protein containing two immunoglobulin superfamily domains. Our previous studies have indicated that overexpression of HAb18G/CD147 enhances metastatic potentials in human hepatoma cells by disrupting the regulation of store-operated Ca2+ entry by nitric oxide (NO)/cGMP. In the present study, we investigated the structure-function of HAb18G/CD147 by transfecting truncated HAb18G/CD147 fragments into human 7721 hepatoma cells. The inhibitory effect of HAb18G/CD147 on 8-brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…These results suggest that HAb18G/ CD147 plays a role in HCC invasion via regulation of MMP production by both tumor cells and surrounding fibroblasts, thus influencing the balance of tumor microenvironment, and the modulation of that by fibroblasts was more critical in the process. Our previous study also showed that HAb18G/ CD147 was involved in tumor metastasis and invasion as a signal transduction molecule by regulating Ca 2+ inflow (25,27). All these findings show that HAb18G/CD147 may play some important roles in HCC progression, including adhesion, migration, and enzymes degradation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These results suggest that HAb18G/ CD147 plays a role in HCC invasion via regulation of MMP production by both tumor cells and surrounding fibroblasts, thus influencing the balance of tumor microenvironment, and the modulation of that by fibroblasts was more critical in the process. Our previous study also showed that HAb18G/ CD147 was involved in tumor metastasis and invasion as a signal transduction molecule by regulating Ca 2+ inflow (25,27). All these findings show that HAb18G/CD147 may play some important roles in HCC progression, including adhesion, migration, and enzymes degradation.…”
Section: Discussionmentioning
confidence: 67%
“…Our previous reports suggested that HAb18G/CD147 was an HCC-associated antigen and was possibly related to HCC invasion in vitro (25)(26)(27). In the present study, we examined the role of HAb18G/CD147 in HCC invasion and metastasis in vitro, and in an orthotopic model of HCC in nude mice.…”
Section: Discussionmentioning
confidence: 83%
“…The CD147 expression vector (CD147-pcDNA3.1) was developed in our laboratory. 36 After cells were grown to 60-80% confluency, transfection was performed using the LipofectAMINE 2000 reagent (Invitrogen) according to the manufacturer's instructions. The pcDNA3.1 empty vector was used as a negative control under similar conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, we recently developed a CD147 mAb, metuzumab, an antibody-dependent cellular cytotoxicity (ADCC)-optimized recombinant human and mouse chimeric with a glycoengineered IgG1 isotype and developed by humanizing and affinity optimizing of the HAb18 mAb (25). Metuzumab is expressed in a fucosyltransferase-deficient CHO cell line, which generates a homogenously afucosylated mAb with increased affinity for FcgIIIA and enhanced ADCC activity.…”
Section: Introductionmentioning
confidence: 99%